Surgical management of advanced gastric cancer: An evolving issue. Issue 1 (January 2016) - Marano, L.; Polom, K.; Patriti, A.; Roviello, G.; Falco, G.; Stracqualursi, A.; De Luca, R.; Petrioli, R.; Martinotti, M.; Generali, D.; Marrelli, D.; Di Martino, N.; et al.
Abstract: Worldwide, gastric cancer represents the fifth most common cancer and the third leading cause of cancer deaths. Although the overall 5-year survival for resectable disease was more than 70% in Japan due to the implementation of screening programs resulting in detection of disease at earlier stages, in Western countries more than two thirds of gastric cancers are usually diagnosed in advanced stages reporting a 5-year survival rate of only 25.7%. Anyway surgical resection with extended lymph node dissection remains the only curative therapy for non-metastatic advanced gastric cancer, while neoadjuvant and adjuvant chemotherapies can improve the outcomes aimed at the reduction of recurrence and extension of survival. High-quality research and advances in technologies have contributed to well define the oncological outcomes and have stimulated many clinical studies testing multimodality managements in the advanced disease setting. This review article aims to outline and discuss open issues in current surgical management of advanced gastric cancer.